18F-fluorodeoxyglucose PET/CT in aplastic anemia: a literature review and the potential of a computational approach. (December 2014) - Piva, Roberta; Fiz, Francesco; Piana, Michele; Bongioanni, Francesca; Bottoni, Gianluca; Bacigalupo, Andrea; Marini, Cecilia; Sambuceti, Gianmario
Aim: Aplastic anemia (AA) is a rare hematologic condition, characterized by bone marrow (BM) insufficiency, mostly on autoimmune basis. BM inhomogeneity hampers the diagnosis by bioptic sample. We propose a noninvasive evaluation of BM extension and metabolism in different AA stages.Materials & methods: Four AA patients (mean age: 45 ± 21, range: 18–63, 3 females) were submitted to whole-body 18 F-fluorodeoxyglucose (FDG) positron emission tomography/computed tomography. We compared these patients with matched healthy controls, selected from a published normalcy database.Results: The presence of several hypermetabolic uptake areas was related to BM hypo/aplasia, while homogeneous, low grade FDG uptake was observed in patients in clinical remission. These data suggest that FDG positron emission tomography/computed tomography could be a noninvasive diagnostic complement in AA patients.